Iron folic acid supplementation adherence level and its associated factors among pregnant women in Ethiopia: a multilevel complex data analysis of 2019 Ethiopian mini demographic and health survey data - Temesgen, Habtamu; Woyraw, Wubetu; Feleke, Fentaw Wassie; Mezgebu, Getachew Sale; Taye, Kefyalew; Awoke, Tadesse (Frontiers in Nutrition, 2024)
Background: Iron and folic acid deficiency is a worldwide public health concern, particularly in low and middle-income countries. In Ethiopia, adherence to iron and folic acid supplements is still very low. Despite the fact that a number of studies on IFA supplementation have been conducted in Ethiopia, they do not indicate a nationwide problem and do not use advanced models to demonstrate clustering effects. The purpose of this study was to assess the level of non-adherence to iron folic acid supplementation and predictors among pregnant women in Ethiopia.Objective: To assess iron folic acid supplementation adherence level and its associated factors among pregnant women in Ethiopia using data from the 2019 Mini-Ethiopian demographic health survey.The Mini Ethiopian Demographic and Health Survey 2019 data were obtained from the official database website of the Demographic and Health Survey program (http://dhsprogram.com). The analysis included a sample of 2356 weighted study participants. A multivariable multilevel mixed-effects logistic regression model was used Variables with pvalues less than 5%) was reported as statistically significant variables in the multivariable analysis.The proportion of mothers who did not adhere to iron and folic acid supplements was 81.03 % (95 %CI: 79.39, 82.56). Birth interval less than two years [AOR: 2.03; 95% CI: 1.12, 3.66], women ever born less than six children [AOR: 1.99; 95% CI: 1.09, 3.64], starting ANC visit during first trimester [AOR: 2.74; 95 %CI: 1.03, 7.30], region [AOR= 0.24; 95% CI: 0.10],and having a high no ANC visit in the community [AOR= 1.77; 95% CI: 1.08, 2.88] were statistically significant factors. There was Intra-Custer Correlation (ICC=17.72 %), indicating that 17.72 % variability in non-adherence levels was due to clustersIn Ethiopia, nearly four out of every five pregnant women did not receive iron folic acid supplementation for the recommended periods. Birth intervals, number of children, timing of ANC visits, region, and community level no ANC service were significant factors for non-adherence IFAS. As a result, the community, govern metal and non-governmental sectors enacting on health should focus on reducing non-adherence through tailored interventions on factors that influence it.